Sosiologi Pendidikan Dalam Pembentukan Karakter Peserta Didik di Sekolah - Santika Virdi; Husnul Khotimah; Kartika Dewi (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This article aims to explain how sociology plays a role in building the character of students. Sociology is a social science that studies facts, norms, and social deviations, which are the main factors in the process of shaping the character of students. This research utilizes a qualitative approach with the research method of literature review, and the data for the study are sourced from literature, journals, and books. In this method, all the obtained data will be analyzed to draw conclusions. The results of this research will indicate that Educational Sociology, as a branch of sociology, plays a significant role in shaping the character of students in schools.